Gambaran Penerapan Sistem Proteksi Aktif Dalam Pencegahan Kebakaran di PT. PLN (Persero) Distribusi Jawa Barat Area Bekasi - Aisyah Firdiani; Herlina Herlina (STIKes Persada Husada Indonesia, 2019)
Every company that employs a workforce of 100 or more people and / or has potential hazards caused by the characteristics of the material production process that can result in work accidents such as: blasting, fire, pollution and occupational diseases, are required to apply SMK3. Fire is caused by various factors, but in general the factors that cause fire are human factors and technical factors. Fire events can be prevented by implementing an active protection system namely fire extinguisher, fire hydrant, detection system, fire alarm. This study aims to determine the description of the application of active protection systems and fire prevention efforts in the office building of PT. PLN (Persero) West Java Distribution Bekasi Area. Qualitative research design with a phenomenological approach, to understand the phenomena about what is experienced by the research subjects. The focus of this study refers to the question of the application of an active protection system in fire prevention efforts, namely fire extinguisher, fire hydrant, detection system, and alarm as well as knowing emergency response procedures, information about potential fire hazards, and lightning protection systems. This research was conducted at PT. PLN (Persero) Bekasi Area Jl. Cut Meutia 44, Margahayu East Bekasi, held on April 2 - 30 April 2018. The sampling method used in this study was puposive sampling. The number of samples that became informants was 6 people. The results of research on active protection systems in PT. PLN (Persero) West Java Bekasi Area Distribution namely APAR is in accordance based on PER.04 / MEN / 1980, Hydrants are partially incompatible based on PU PERMEN NO.26 / PRT / M / 2008, Detection Systems are in accordance based on PER.02 / MEN / 1983, and the Fire Alarm is not yet according to PER.02 / MEN / 1983. It is recommended to PT. PLN (Persero) Distribution West Java Bekasi Area repaired immediately by replacing the new one from the elements of the active protection system that was damaged namely Hydrant and Fire Alarm and installed a detection system in the new room of the PDKB.